Tambores da Revolução: Moçambique, colonialismo e independência a partir da obra de Paulina Chiziane - Sanchez, Marcelo Hailer (2019)
This thesis is the result of a border crossing of a Brazilian body that landed in Mozambique accompanied by Fanon and Spivak, but completely alienated on the history of the country in southern Africa. It was in everyday conversations, in the bars and in the streets of Maputo, that the epistemological colonization gained form and meaning. From this understanding, we carry out a critical and historical panorama of the Studies of Subalternity and Decolonial. With the theoretical and methodological assumptions of both currents, we analyze the question of the coloniality of power present in the field of Social Sciences, which still privileges the colonial knowledge produced in Europe. Later, in dialogue with the mozambican writer Paulina Chiziane, we analyzed the mozambican revolution and the role of women in the guerrillas that won the country's independence. In the final part of this thesis, we interviewed Chiziane to discuss the legacies of the communist revolution led by FRELIMO, the danger of neocolonialism and literature as an important tool to break with the epistemological domain and the colonization of mentalities